Perancangan Sistem Informasi Penjualan Menggunakan Metode Rapid Application Development Berbasis Website (Studi Kasus : Toko Ayoh Original Distro - Dwi Haryanto, Fauzi; Haerudin, Heri (CV. Shofanah Media Berkah, 2024)
Ayoh Original Distro Store is a business related to distro clothing sales services, in its operation the Ayoh Original Distro Store still has several problems, namely the absence of online transaction facilities so that the sale of goods is still carried out by visiting the store, recording sales reports is done manually so that there are often errors in inaccurate report data and nominal differences in sales. In overcoming this problem, the author conducted a study to create an application for a sales recording information system using the Rapit Application Development method. With the design of a web-based information system, Toko Ayoh Original Distro can help store employees in storing sales report data more efficiently and recording transaction reports more efficiently. In this study, the author used a programming language, namely Hypertext Prepocessor (PHP), as well as a MySQL database as a storage for employee complaint data and a Rapid Application Development (RAD) Model in creating the design flow. With this sales system application, the author hopes to make it easier for the Ayoh Original Distro Store to record sales transactions and be able to store sales report data easily and quickly so that it can save time.